Transition-state stabilization in the mechanism of tyrosyl-tRNA synthetase revealed by protein engineering. - Leatherbarrow, R J (1985)
The principal catalytic factor in the activation of tyrosine by the tyrosyl-tRNA synthetase is found to be improved binding of ATP in the transition state. The activation reaction involves the attack of the tyrosyl carboxylate on the alpha-phosphate group of ATP to generate a pentacoordinate transition state. Model building of this complex located a binding site for the gamma-phosphate group of ATP, consisting of hydrogen bonds with the side chains of Thr-40 and His-45. Removal of these groups by protein engineering shows that they contribute no binding energy with unreacted ATP but put all of their binding energy into stabilizing the [tyrosine-ATP] transition state [the mutant tyrosyl-tRNA synthetase (Thr-40----Ala-40; His-45----Gly-45) has the rate of formation of tyrosyl adenylate lowered by 3.2 X 10(5) but KS for ATP is lowered by only a factor of 5]. The side chains of these residues also provide a binding site for pyrophosphate in the reverse reaction. Thus, catalysis is accomplished by stabilization of the transition state by improved binding of a group on the substrate that is distant from the seat of reaction.